MODEL PEMBELAJARAN PROJECT BASED LEARNING DENGAN MEMANFAATKAN APLIKASI PORTABLE MONOPOLY PADA PELAJARAN DASAR AKUNTANSI GUNA MENGEMBANGKAN CHARACTER BUILDING WARGA BELAJAR DI SMK JOSUA JAKARTA - Safri Safri; Iswandir Iswandir (JURNAL MITRA MANAJEMEN, 2019)
Science and knowledge are sourced from the almighty knowledge, God provides knowledge and knowledge that is useful to his people based on the correct adaptation, Humans must definitely give you, humans give you much, certainly not necessarily. Teachers are only the facilitators in suing you, hoping that they will provide a glimpse of your knowledge on you’re sharing, teachers are required to develop themselves with learning methods. Classroom Action Research using Project Based Learning Method with Portable Monopoly Application in Accounting Cycle learning implemented at SMK Josua Jakarta provides improved results in terms of skills, knowledge, and attitudes in class XI learners compared to conventional methods, where there is an increase in knowledge, brush, and work ethic of 14.79% It is hoped that in the future this method can be continued and improved again by developing the use of the adroid application so that it is more updated with the development of the millennial era or 4.0